The identification of alcohol percentage limit in halal food using fuzzy logic - Mohd Ali, Jarinah; Othman, Suhaili; Ahmad Fadzillah, Nurrulhidayah; Abd. Rahman, Norliza (Springer Nature Singapore Pte Ltd, 2021)
Based on Islamic Law, several types of alcohol have been found to be intoxicated liquid or drink that may affect a person’s rationality. In the food industry, alcohol can be divided into two. First, alcohol that is derived from the process of wine-making or other alcoholic beverages (khamar) that is prohibited and impure (najs) and second, alcohol that is made from other processes which exclude the alcoholic beverages-making processes, that is not impure yet prohibited to be consumed. It is difﬁcult to identify the percentage of alcohol according to the Fatwa in compliance with the manufacturing standards, since the product label does not usually give an accurate information. Several approaches have been employed to identify the content of alcohol in food and drinks such as gas chroma- tography and polymerase chain reaction, which are hardware driven, slow and require high maintenance. As an alternative, fuzzy logic has been applied for the identiﬁcation of the halal alcohol limit due to its advantages, including it is more economical (software-based), provide fast authentication and reliable. It is also easy to adjust or tune to cater to changes of any standards, since fuzzy logic is implemented using rules that may be adjusted according to the laws and regulations outlined by JAKIM from time to time. The algorithm will be developed to determine the permissibility level in such a way that it can identify the status of both the food and drinks containing alcohol whether it complies with JAKIM’s standard or not based on the percentage. This algorithm and basic framework will be the first step in developing a user-friendly tool that will later benefit the consumer as well as function as an auditor especially in order to control the alcohol content in halal food and beverages.